How Older Female Spouses Cope with Partners' Coronary Artery Bypass Graft Surgery - Suzanne Marnocha; Mark Marnocha (Hindawi Limited, 2013)
This research sought to better understand how older female spouses cope with a partner's coronary artery bypass graft surgery and to explore coping's relationships with life-change stress, cognitive appraisal, resilience, social support, and aspects of spouse's surgery. A sample of 96 women, aged from 55 to 81 years, completed surveys after their partner's surgery. Folkman and Lazarus' ways of coping (WCQ) scales yielded two factors in this sample-reactive coping and adaptive coping. Reactive coping, including more emotion-focused ways of coping from the WCQ, was associated only with more time spent anticipating spouses' surgeries. Women described the greatest use of ways of coping labeled adaptive, which in turn had significant relationships with greater resilience, social support, and positive appraisal of the surgical experience. Stepwise multiple regression found greater resilience, more frequent religious participation, and fewer children to be distinct predictors of adaptive coping. Nursing staff are encouraged to accept and normalize reactive coping, while facilitating adaptive coping with surgical stresses.